2013
DOI: 10.1007/s00018-013-1262-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of NMDA receptors in adult neurogenesis: an ontogenetic (re)view on activity-dependent development

Abstract: It is now widely accepted that neurogenesis continues throughout life. Accumulating evidence suggests that neurotransmitters are essential signaling molecules that control the different steps of neurogenesis. Nevertheless, we are only beginning to understand the precise role of neurotransmitter receptors and in particular excitatory glutamatergic transmission in the differentiation of adult-born neurons. Recent technical advances allow single-cell gene deletion to study cell-autonomous effects during the matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 87 publications
1
10
0
1
Order By: Relevance
“…They might help to modulate proliferation and shift determination of daughter cells towards neuronal fate in an activity‐dependent manner (Deisseroth et al 2004). Furthermore, it was also reported that neuronal progenitors and neuroblasts continue to express ionotropic glutamate receptors which were suggested to restrict migration and regulate positioning of newborn neurons dependent on glutamate spillover from neighbouring synapses (Namba et al 2011; Platel & Kelsch, 2013). Therefore, it is not surprising that the postmitotic newborn granule cells express functional extrasynaptic ionotropic glutamate receptors even before synaptic integration.…”
Section: Discussionmentioning
confidence: 99%
“…They might help to modulate proliferation and shift determination of daughter cells towards neuronal fate in an activity‐dependent manner (Deisseroth et al 2004). Furthermore, it was also reported that neuronal progenitors and neuroblasts continue to express ionotropic glutamate receptors which were suggested to restrict migration and regulate positioning of newborn neurons dependent on glutamate spillover from neighbouring synapses (Namba et al 2011; Platel & Kelsch, 2013). Therefore, it is not surprising that the postmitotic newborn granule cells express functional extrasynaptic ionotropic glutamate receptors even before synaptic integration.…”
Section: Discussionmentioning
confidence: 99%
“…1b), with nonsynaptic, ambient GABA as the first input and synaptic glutamate from Ent as the last 33,35,83 . Taken together with the fact that new neurons have a lower threshold for firing relative to embryonic-generated neurons and that they are sensitive to activity-dependent regulation 36,8587 , the emerging view is that immature adult-generated DG neurons are distinct from mature adult-generated and all embryonic-generated DG neurons in that they are “young and excitable” 88 , function independently of inhibitory GABA circuits 89 and receive direct innervation from their glutamatergic “elders” 84 . In fact, some work suggests that adult-generated neurons remain functionally distinct from their embryonic-generated counterparts 90 .…”
Section: Adult Dg Neurogenesismentioning
confidence: 99%
“…These neurons become granule cells (GCs), the principal neurons in the dentate gyrus (DG) of the hippocampus, and they functionally integrate into the hippocampal circuitry ( van Praag et al, 2002 ; Toni et al, 2008 ). This extreme form of structural remodeling, similar to many other forms of experience-dependent plasticity, requires activation of NMDA receptors (NMDARs) ( Platel and Kelsch, 2013 ). Blockade of NMDARs rapidly increases the proliferation of neural precursor cells, whereas stimulation of NMDARs promotes neuronal fate specification ( Cameron et al, 1995 ; Deisseroth et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%